Ectomycorrhizal Fungi on South Kalimantan Serpentine Soil - Rudy Hermawan; Witiyasti Imaningsih; Badruzsaufari Badruzsaufari (Jurnal Mikologi Indonesia, 2020)
Serpentine soil contains highly heavy metals, such as manganese, chromium, cobalt, and nickel,which could bean inappropriate growthmediaofmostplants. Someplants thatfound able to grow optimally on South Kalimantan serpentine soil have been known to do association with ectomycorrhizal fungi. This research aimed to obtain and characterize mushrooms assumed as ectomycorrhizal fungi indigenous South Kalimantan serpentine soil. This study used field exploration of fungal fruiting bodies and identified the genus based on morphological characters of fruiting bodies such as shape, size, and ornamentation, which are unique for the genus identification, then compared the characteristics on mushroomexpert.com. The mushrooms were also confirmed of genera assumed as ectomycorrhizal fungi based on mycorrhizas.info. Seven fruiting bodies were obtained and classified as Cantharellus (Ct), Chlorophyllum (Ch1 and Ch2), Lycoperdon (Ly), Ramaria (Rm1 and Rm2), and Thelephora (Tp). The results showed that all of those fruiting bodies belong to Basidiomycetes. There were 4 genera of Cantharellus, Lycoperdon, Ramaria, and Thelephora, assumed as ectomycorrhizal fungi. But Chlorophyllum genus was never reported as ectomycorrhizal fungus